Sepsis, Failure of Passive Transfer, and Fluid Therapy in Calves. - Amanda M. House; Max Irsik; Jan K. Shearer (EDIS)
VM-173, a 5-page fact sheet by Amanda M. House, Max Irsik, and Jan K. Shearer, describes septicemia and neonatal infection in calves, how to ensure adequate passive antibody transfer as a preventative health measure, and how to manage fluid therapy for dehydrated calves. Includes references. Published by the UF School of Veterinary Medicine, August 2008.